Maintaining a Long-Distance Marriage: Communication and Spirituality (Journal of Family Sciences, 2025)
Long-distance marriage (LDM) can pose significant challenges for couples in preserving emotional intimacy, trust, and overall relationship stability, highlighting the importance of resilience in sustaining connections. This study investigated the interplay between spirituality, WhatsApp communication, and resilience in long-distance marriages. Resilience encompasses a couple's ability to effectively navigate challenges within a long-distance marriage (LDM). This study employed a quantitative correlational design and included 138 married individuals who have been engaged in LDM for at least one year. Data collection involved questionnaires assessing WhatsApp communication, spirituality measured by the Daily Spiritual Experiences Scale (DSES), and couple resilience evaluated through the Couple Resilience Inventory Scale (CRIS). Analyses were performed using IBM SPSS. The results indicated a positive correlation between WhatsApp communication and positive resilience behaviour (r = 0.489, p < 0.01), along with a negative correlation with negative resilience behaviour (r = -0.442, p < 0.01). Furthermore, spirituality exhibited a positive correlation with positive resilience behaviour (r = 0.422, p < 0.01) and a negative correlation with negative resilience behaviour (r = -0.299, p < 0.01). WhatsApp communication and spirituality accounted for 28.6% of the variance in couple resilience, with other factors influencing the remaining percentage. These findings suggest that both digital communication and spirituality play significant roles in enhancing resilience among couples in long-distance relationships.